Evaluation of Efficacy of Coenzyme Q10 as an Adjunct to Nonsurgical Periodontal Therapy and Its Effect on Crevicular Superoxide Dismutase in Patients with Chronic Periodontitis - Pranam, Swagat; Palwankar, Pooja; Pandey, Ruchi; Goyal, Anjana (European Journal of Dentistry, 2020)
Objectives To assess the efficacy of coenzyme Q10 (CoQ10) as an adjunct to nonsurgical periodontal therapy and its effect on superoxide dismutase (SOD) in gingival crevicular fluid (GCF) in patients with chronic periodontitis (CP).Materials and Methods A total of 16 patients aged between 30 and 50 years having mild to moderate CP of both sexes having pocket depth of 5 to 7 mm in four nonadjacent interproximal sites were selected. The sites were randomized and divided into treatment and control groups. CoQ10 and a placebo gel were administered in the treatment and control sites, respectively, at baseline after scaling and root planing (SRP). GCF was collected using microcapillary method at baseline and 3 months and was assessed for SOD using enzyme-linked immunosorbent assay reader at 450 nm wavelength. Probing pocket depth, gingival index, and plaque index were assessed at baseline, 1 month, and 3 months, respectively.Statistical analysis For each assessment point, data were statistically analyzed using Student’s t-test and paired t-test. Level of significance was set at p < 0.05.Results On intergroup comparison, there was no statistically significant difference between the clinical parameters of both the groups at all the time intervals (p > 0.05), but there was a significant increase in the level of SOD in the test group (p > 0.05) compared with the control group at 3 months.Conclusions Adjunctive use of CoQ10 with SRP can boost the antioxidant concentration, but it is not superior to SRP in the treatment of CP.
Keywords: chronic periodontitis; coenzyme Q10; ELISA; gingival crevicular fluid; superoxide dismutase